Determination of the optimal sanding sequence for Freijó wood (Cordia goeldiana Huber) to achieve the best surface roughness for furniture purposes (Research, Society and Development, 2024)
The use of exotic species in commercial plantations is a reality in the current scenario of the Brazilian timber sector; however, there is limited utilization of the wide range of native species with productive potential for the same purpose. Therefore, studies are necessary to facilitate the introduction of native species in various timber-related fields, such as the furniture industry. One of the numerous species that stand out in this sector is Freijó (Cordia goeldiana Huber), as it possesses aesthetic and mechanical characteristics attractive for this purpose. Thus, the present study aims to evaluate characteristics that influence the surface quality of wood, including roughness. The parameters analyzed by the drag-type profilometer were Ra, Rq, and Rz after Freijó wood underwent treatment with abrasives of different grit sizes. The generated results were analyzed using the SISVAR statistical program, employing Completely Randomized Design (CRD), ANOVA, and the Scott-Knott Test, both at a 5% significance level. In conclusion, the recommendation is to use abrasives with grit sizes of 80 – 120 – 180 - 220, as they proved to be enough for achieving a surface that meets the requirements of the furniture industry.